Impact of tocilizumab on N-terminal pro-brain natriuretic peptide levels in patients with active rheumatoid arthritis without cardiac symptoms. (3rd September 2018) - Yokoe, I; Kobayashi, H; Kobayashi, Y; Giles, JT; Yoneyama, K; Kitamura, N; Takei, M
Abstract : Objective : To prospectively investigate the effect of tocilizumab (TCZ) on the levels of N-terminal pro-brain natriuretic peptide (NT-proBNP), as a predictor of congestive heart failure (CHF) in patients with active rheumatoid arthritis (RA). Method : Seventy patients with RA (median age 59 years, 86% female) free of cardiovascular disease were treated with TCZ and followed for 24 weeks. The NT-proBNP levels were measured at baseline and week 24. Thirty healthy controls were included for comparison of normal NT-proBNP levels with those of RA patients. Results : The NT-proBNP level was significantly higher in patients with RA than in controls (median 42.5 pg/mL vs 109.0 pg/mL, p < 0.001). NT-proBNP levels decreased by 63% over the 24 weeks of TCZ treatment. Multiple linear regression analysis indicated that the percentage change in the NT-proBNP level was significantly associated with that of the Simplified Disease Activity Index (β = 0.356, p = 0.014), even after adjusting for the levels of rheumatoid factor, duration of RA, age, and anti-cyclic citrullinated peptide antibody. Conclusion : TCZ decreased the NT-proBNP level in patients with RA without preceding cardiovascular disease and CHF. TCZ may have a cardioprotective effect in those with active RA.